Investigation of the effects of Ni-doping on the structural and thermal properties of ZnAl2O4 spinels prepared by wet chemical method - Ercan, Filiz; Ates, Tankut; Kaygili, Omer; Bulut, Niyazi; Koytepe, Suleyman; Alahmari, Fatimah; Hssain, Ala Hamd (Springer, 2021)
In this study, a more detailed characterization of the un-doped and Ni-doped ZnAl2O4 spinel structures prepared via a facile wet chemical route was carried out. Significant effects of the additive of Ni on the ZnAl2O4 structure were observed. For all the samples, the ZnO phase was detected as the second phase, and the third phase of NiO was observed for two samples having the highest Ni content. X-ray diffraction (XRD) results showed that the crystallinity percent, lattice parameter, and volume of the unit cell decreased continuously with adding of Ni. Fourier transform infrared (FTIR) spectra verify the formation of the ZnAl2O4 structure for all the samples. The thermal behaviors, including the recrystallization temperature and mass losses, of the ZnAl2O4 structure, were also affected by the amount of Ni. The morphology varied with adding of Ni. These properties were not reported before.
Keywords: Spinel; Wet chemical method; Crystal structure